Age-Dependent Decline in Cardiac Function in Guanidinoacetate-N-Methyltransferase Knockout Mice - Aksentijević, Dunja; Zervou, Sevasti; Eykyn, Thomas R.; McAndrew, Debra J.; Wallis, Julie; Schneider, Jurgen E.; Neubauer, Stefan; Lygate, Craig A. (Frontiers in Physiology, 2020)
Aim: Guanidinoacetate N-methyltransferase (GAMT) is the second essential enzyme in creatine (Cr) biosynthesis. Short-term Cr deficiency is metabolically well tolerated as GAMT-/- mice exhibit normal exercise capacity and response to ischaemic heart failure. However, we hypothesised long-term consequences of Cr deficiency and/or accumulation of the Cr precursor guanidinoacetate (GA). Methods: Cardiac function and metabolic profile were studied in GAMT-/- mice >1 year. Results: In vivo LV catheterisation revealed lower heart rate and developed pressure in ageing GAMT-/- but normal lung weight and survival versus age-matched controls. Electron microscopy indicated reduced mitochondrial volume density in GAMT-/- hearts (P<0.001), corroborated by lower mtDNA copy number (P<0.004), and citrate synthase activity (P<0.05) however without impaired mitochondrial respiration. Furthermore, myocardial energy stores and key ATP homeostatic enzymes were barely altered, while pathology was unrelated to oxidative stress since superoxide production and protein carbonylation were unaffected. Gene expression of PGC-1α was 2.5-fold higher in GAMT-/- hearts while downstream genes were not activated, implicating a dysfunction in mitochondrial biogenesis signalling. This was normalised by 10 days of dietary Cr supplementation, as were all in vivo functional parameters, however, it was not possible to differentiate whether relief from Cr deficiency or GA toxicity was causative. Conclusion: Long-term Cr deficiency in GAMT-/- mice reduces mitochondrial volume without affecting respiratory function, most likely due to impaired biogenesis. This is associated with haemodynamic changes without evidence of heart failure, which may represent an acceptable functional compromise in return for reduced energy demand in ageing mice.